2016
DOI: 10.1177/0009922815615825
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety, and Severity of Obesity in Adolescents

Abstract: The purposes of this study were to characterize the impact of depression and anxiety on the severity of obesity among youth seeking weight management treatment and to determine the extent to which emotional eating mediates the relationship between depression and/or anxiety and degree of obesity. This cross-sectional, retrospective chart review of 102 adolescent patients from a weight management clinic analyzed demographics, body mass index (BMI), depression (Patient Health Questionnaire-9) and anxiety (General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
63
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 32 publications
4
63
1
9
Order By: Relevance
“…For example, dietary restraint as well as prolonged periods of starvation often leads to depressive‐like symptoms such as emotional instability and lethargy . Emotional eating, on the other hand, usually manifests as a mechanism to cope with negative affect . When in reaction to anxiety, emotional eating acts as a biological response to limit hyperarousal, and in reaction to depression, it provides temporary feelings of gratification/satisfaction .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dietary restraint as well as prolonged periods of starvation often leads to depressive‐like symptoms such as emotional instability and lethargy . Emotional eating, on the other hand, usually manifests as a mechanism to cope with negative affect . When in reaction to anxiety, emotional eating acts as a biological response to limit hyperarousal, and in reaction to depression, it provides temporary feelings of gratification/satisfaction .…”
Section: Discussionmentioning
confidence: 99%
“…44 When in reaction to anxiety, emotional eating acts as a biological response to limit hyperarousal, 44 and in reaction to depression, it provides temporary feelings of gratification/satisfaction. 44 Although emotional eating serves to alleviate aversive feelings in the short-term, it often exacerbates these feelings over time. 45 Parenting style, specifically the use of psychological control over the child (ie, attempting to manipulate the child's actions, thoughts, and emotions), was associated with both child depression and anxiety symptoms in the full models; this is the first study to show the relation between psychological control over child and mental health status among children with OW/OB.…”
Section: Discussionmentioning
confidence: 99%
“…One representative study of adolescents with obesity found that after adjusting for demographics and emotional eating, the odds of having severe obesity versus obesity were 3.5 times higher for patients with depression (as measured by PHQ-9; a score ³ 11 was considered depression) compared with those without (OR = 3.5; 95% CI 1.2,20.9, p = 0.030). 31 Similarly, the odds of having severe obesity were also higher with anxiety (Generalized Anxiety Disorder Scale ³ 10), OR = 4.93, 95% CI = 1.17,20.85, p = 0.030). In this study, there was no association of either depression or anxiety with emotional eating, but other studies have found emotional eating as a mediator for obesity in individuals with depression.…”
Section: Discussionmentioning
confidence: 90%
“…A body of literature demonstrates the association of emotional dysregulation with weight gain and obesity. 12,31,37,38 It has been suggested in adults, that a poor emotional regulation may entail the use of maladaptive strategies to manage emotions and stress, for example, by using highly palatable and energy dense food to suppress emotions. 39 Studies in children have demonstrated that emotional eating is often followed by negative emotions, [40][41][42][43] and is likely to be a learned behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed a relatively higher prevalence of psychological problems among obese children compared with that of this study. For example, in a sample of 102 adolescent patients from a weight management clinic, 34% had depressive symptoms and 32% had symptoms of anxiety [26]. A cross-sectional study in Canada found that depressive symptoms were common (36.4%) in youth with obesity [27].…”
Section: Discussionmentioning
confidence: 99%